2019
DOI: 10.1016/j.engfailanal.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

A testing platform for subsea power cable deployment

Abstract: The failure of subsea cables has been predominantly attributed to third party activities and cable field joints. Field joints may be unavoidable due to joining of insufficient factory-made cable lengths, cable repair, or when the cable installation process has to be abandoned due to rough weather or other unplanned events. Failures within the jointing location reveal that current quality testing of these joints may be inadequate. The failure mode in these joints is mainly a result of seawater ingress at the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…P = e z 1 e z 1 + e z 2 (4) where P represents the probability that the proposed region contains diagnostic objects; z 1 and z represent the foreground score and background score of proposed regions, respectively. After each convolutional layer, the ReLU layers are applied to enhance the nonlinear characteristics, and the ReLU function is given in (3).…”
Section: Region Proposal Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…P = e z 1 e z 1 + e z 2 (4) where P represents the probability that the proposed region contains diagnostic objects; z 1 and z represent the foreground score and background score of proposed regions, respectively. After each convolutional layer, the ReLU layers are applied to enhance the nonlinear characteristics, and the ReLU function is given in (3).…”
Section: Region Proposal Networkmentioning
confidence: 99%
“…Cable accessories, which are used to connect cables with other electrical equipment or different sections of cables, are the weak links of cable systems [2]. Reference [3,4] indicated that the manufacturing of fault-free cable accessories is almost impossible, and poor workmanship during installations and design defects may result in cable faults. Previous studies showed that when there exist defects in cable accessories, such as poor contact of metal connectors, misalignment of stress cones, damage of insulation layer or impurities, and bubbles in the internal medium, the temperature of defective cable accessories was usually higher than those fault free cable accessories [5].…”
Section: Introductionmentioning
confidence: 99%
“…Reda et al [3] indicated that 35.4%, 22.9% and 11.5% of all failures in the medium voltage subsea power cable system in Greece were related to anchoring, fishing and instability events, respectively, as shown in Figure 1. Figure 2 shows a proportion of cable faults by cause, from a database containing 2,162 records spanning the years 1959-2006 [1].…”
Section: Is Abrasion An Issue?mentioning
confidence: 99%
“…Submarine power cables and umbilicals are becoming increasingly common features of offshore hydrocarbon field development and renewable wind farms [1,3,4]. The on-bottom stability design of the subsea cables and umbilicals tend to use the ultimate limit state, accidental limit state and serviceability limit state.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, an engineering challenge faced by pipe designers includes sustainable design methods, safe operating procedures, and better monitoring techniques [8][9][10][11]. The safety and protection of SURF (subsea cables, umbilicals, risers, and flowlines) systems have increased demand in the industry [12][13][14][15][16][17]. Aside from protection, material choice is also important for long service and for preventing any structural failure.…”
Section: Introductionmentioning
confidence: 99%